Antibiotics Susceptibility Pattern of Escherichia coli Strains Isolated from Chickens with Colisepticemia in Tabriz Province, Iran - Salehi, T. Zahraei; Bonab, S. Farashi (International Journal of Poultry Science, 2006)
Antimicrobial agents are used extremely in order to reducing the enormous losses caused by Escherichia coli infections (colibacillosis) in Iran poultry industry. In this investigation fifty avian pathogenic Escherichia coli (APEC) strains isolated from broiler chickens with colisepticemia and examined for susceptibility to antimicrobials of veterinary and human significance. In vitro antibiotic activities of 32 antibiotic substances against the isolates were determined by disc diffusion test (Kirby Bauer method). Multiple resistances to antibiotics were observed in all the isolates. The highest rate of resistance was against Nalidixic acid (100%), Lincomycin (100%), Erythromycin (97%), Oxytetracycline (95%), Chlortetracycline (95%), Tetracycline (94%), Flumequine (94%), Tiamulin (91%), Doxycycline (88%), Difloxacin (83%), Neomycin (81%), Streptomycin (81%), Trimethoprim-Sulphamethoxazole (80%), Kanamycin (77%), Enrofloxacin (76%), Norfloxacin (68%), Ciprofloxacin (67%), Chloramphenicol (67%), Furazolidone (66%), Nitrofurantoin (56%), Amoxicillin (53%) and Ampicillin (47%). Resistance to Gentamicin wasn`t observed and to Amikacin, Cefazolin, Colistin, Tobramycin, Ceftizoxime, Cefixime, Lincospectin, Ceftazidime and also Florfenicol were low. This study showed resistance rate against the antibiotics that are commonly used in poultry is very high but against them that are only used in human or less frequently used in poultry is significantly low. These findings confirm significant increase in the incidence of antimicrobial resistance in the E. coli strains is most probably due to increased use of antibiotics as feed additives for growth promotion and prevention of diseases, use of inappropriate antibiotics for treatment of diseases, resistance transfer among different bacteria and possible cross resistance between antibiotics used in poultry. This study also showed that the prevalence of Quinolone-Resistant Escherichia coli (QREC) is very high in broiler farms in Tabriz province. The high presence of QREC from broiler chickens probably is due to overuse of enrofloxacin in these farms for therapeutic purposes. The present study suggests introduction of surveillance programs to monitor antimicrobial resistance in pathogenic bacteria is strongly needed because other than animal health problems, transmission of resistant clones and resistance plasmids of E. coli from food animals (especially poultry) to humans can occur.